Experimental investigation on vapor-pump equipped gas boiler for flue gas heat recovery. (25th January 2019) - Wei, Maolin; Fu, Lin; Zhang, Shigang; Zhao, Xiling
Highlights: Experiment of the vapor-pump system for flue gas heat recovery is conducted. System performance is fully discussed basing on measured data. Boiler thermal efficiency is significantly improved after heat recovery. The boiler pollutants emission concentrations are significantly reduced. The system owns good economic with a short payback period. Abstract: To recycle the flue gas waste heat, a vapor-pump system is built and its performance is fully discussed in this paper. The vapor-pump system consists of a gas condenser, an air humidifier and a gas-water heat exchanger. The boiler oxidizing air is heated and humidified in the air humidifier. Thus the dew point of the boiler outlet flue gas is improved to above 60 °C. Then in the gas-water heat exchanger, the waste heat is recovered by the heating network return water. According to the experiment results, the exhaust flue gas temperature is reduced from 80–30.9 °C. The system efficiency improvement reaches over 10%. The return water temperature, the ambient air wet bulb temperature and the circulation water mass flow rate affect the system performance markedly. The system performance changes during a whole winter are simulated. Besides of energy saving, the vapor-pump system also can reduce the pollutant emission concentration. If the air is heated to over 50 °C, the concentration of NOx decreases from 33–24.6 ppm, the reduction is about 25.4%. The vapor-pump system achieves energy saving and emission reduction simultaneously. Techno-economic analysis is also proposed in this paper, the payback period is only 0.7 year.